Mutualismo societario en Navarra a comienzos del siglo XX: la protección de la mujer a través de los socorros post-mortem - Sola Ayape, Carlos (Huarte de San Juan. Geografía e Historia, 1998)
The investigation is a wager for knowing the mutual benefit society's characteristics in Navarra of the late nineteenth century and the beggining from twentieth century, made for economical assisting to the women after husband's death. So we make out the importance mutual practice thought in order to lessen one of the reason in the porverty's feminity: the widowhood. The historical context is a protagonist, because happens a estructural change of a great importance: from tradicional formulas of the aids to the widowed and orphon, to save's formulas and workers' periodical current price for getting personal laws about a future indemnity. This is a step from unforeseen to foreseen, about solidarity, reciprocity and mutual aid. A mutual develope that originates a polihedral associationism, whose interpretation reachs the limits played by an aid to some beneficiaries. This mutualism is thought from new burgher values, between them, foreseen, save, morality and family.
Keywords: Mutual benefit societies; Navarra; 19th and 20th centuries